(untitled) (Update Dental College Journal, 2019)
Background: Orthopantomograph (OPG) is one of the most common radiograph use by dental surgeon for evaluate information about teeth, Maxilla, Mandible and other bony structure. It is also available, low price and low doses of radiation. Mandibular condyle is most important landmarks of mandible, which is changes due to ageing process, developmental abnormalities, distinct diseases, trauma, endocrine shock, radio therapy etc. Panoramic radiographs remain the best screening modality for temporomandibular joint abnormalities today. Objectives: The aims at objective of observing and documentation of shapes of condyle on an orthopantomogram, which were very important for treatment of patient in different branch of dentistry specially in oral and maxillofacial surgery. Materials and Methods: This study composed radiographic evaluation of 500 condylar heads after imaging 250 digitalized OPGs taken for analysis. Then evaluate the mandibular condylar shape in 2D dimensional view (OPG). Results: In our study, an attempt to common prevalent radiographic shapes of the condylar head on the OPG. 200 pairs of condylar heads were evaluated. Out of them 60% were oval in shape, followed by bird beak (29%), diamond (9%) and least being crooked finger (2%). Oval-oval was commonly occurring mix (67%), whereas crooked/ crooked finger was a rarity. Conclusion: Due to low radiation exposer and availability, OPG is common chose of dentist for primary evaluate the tooth, mandible and facial skeleton. Shapes of the mandibular condyle also evaluate by OPG which showing ovaloval being most accepted in both genders. Update Dent. Coll. j: 2019; 9 (1): 29-31